Characterization, bio-uptake and toxicity of polymer-coated silver nanoparticles and their interaction with human peripheral blood mononuclear cells - Pourhoseini, Sahar; Enos, Reilly T.; Murphy, Angela E.; Cai, Bo; Lead, Jamie R. (Beilstein Journal of Nanotechnology, 2021)
Silver nanoparticles (AgNPs) are widely used in medical applications due to their antibacterial and antiviral properties. Despite the extensive study of AgNPs, their toxicity and their effect on human health is poorly understood, as a result of issues such as poor control of NP properties and lack of proper characterization. The aim of this study was to investigate the combined characterization, bio-uptake, and toxicity of well-characterized polyvinylpyrrolidone (PVP)-coated AgNPs in exposure media during exposure time using primary human cells (peripheral blood mononuclear cells (PBMCs)). AgNPs were synthesized in-house and characterized using a multimethod approach. Results indicated the transformation of NPs in RPMI medium with a change in size and polydispersity over 24 h of exposure due to dissolution and reprecipitation. No aggregation of NPs was observed in the RPMI medium over the exposure time (24 h). A dose-dependent relationship between PBMC uptake and Ag concentration was detected for both AgNP and AgNO3 treatment. There was approximately a two-fold increase in cellular Ag uptake in the AgNO3 vs the NP treatment. Cytotoxicity, using LDH and MTS assays and based on exposure concentrations was not significantly different when comparing NPs and Ag ions. Based on differential uptake, AgNPs were more toxic after normalizing toxicity to the amount of cellular Ag uptake. Our data highlights the importance of correct synthesis, characterization, and study of transformations to obtain a better understanding of NP uptake and toxicity. Statistical analysis indicated that there might be an individual variability in response to NPs, although more research is required.
Keywords: human peripheral blood mononuclear cells; silver ions; silver nanoparticles; toxicity; uptake